The 2-point method: Theoretical basis, methodological considerations, experimental support, and its application under field conditions - García-Ramos, A. (International Journal of Sports Physiology and Performance, 2023)
The "2-point method," originally referred to as the "2-load method," was proposed in 2016 by Prof Slobodan Jaric to characterize the maximal mechanical capacities of the muscles to produce force, velocity, and power. Two years later, in 2018, Prof Jaric and I summarized in a review article the scientific evidence showing that the 2-point method, compared with the multiple-point method, is capable of providing the outcomes of the force-velocity (F-V) and load-velocity (L-V) relationships with similar reliability and high concurrent validity. However, a major gap of our review was that, until 2018, the feasibility of the 2-point method had only been explored through testing procedures based on multiple (more than 2) loads. This is problematic because (1) it has misled users into thinking that implementing the 2-point method inevitably requires testing more than 2 conditions and (2) obtaining the data from the same test could have artificially inflated the concurrent validity of the 2-point method. To overcome these limitations, subsequent studies have implemented in separate sessions the 2-point method under field conditions (only 2 different loads applied in the testing protocol) and the standard multiple-point method. These studies consistently demonstrate that while the outcomes of the 2-point method exhibit comparable reliability, they tend to have slightly higher magnitudes compared with the standard multiple-point method. This review article emphasizes the practical aspects that should be considered when applying the 2-point method under field conditions to obtain the main outcomes of the F-V and L-V relationships.